PROJECT-BASED LEARNING ON THE DEVELOPMENT OF TEACHING MEDIA BASED ON INFORMATICS AND COMMUNICATIONS (ICT): GOOGLE SITE FOR ENGLISH TEACHERS MGMP RAYON 5 CITY OF JAMBI - Wira Pratama, Arya; Mahmudah, Khotimah; Fitria, Wahyuni; Rozal, Edi; Sastra Sumardi, Mayang; Putri, Rahmadani; Nirwana, Iin; Ramdayeni Sakunti, Sri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Google site is one of the media that can be used in distance learning. This media can be integrated with a website to facilitate the process of distributing materials and assignments to students. This community service activity uses the Project-based Learning method aimed at English teachers at MGMP Rayon 5 Jambi City where teachers are given work projects to make technology-based teaching materials through Google-site and then integrated through the teacher's account at "Belajar.id". The purpose of this activity is to provide teachers with experience and knowledge on how to make English teaching materials through the google-site and integrate these teaching materials into the teacher's Belajar.id account. The results of teacher interviews about this activity showed that the Google-Sites training was beneficial for them to understand how to create, input, and distribute teaching materials through Google-Sites.